Papel da asparagina em diferentes processos na biologia de Trypanosoma cruzi. - Araujo, Rosana Beatriz Duque (2014)
Chagas disease, is caused by the protozoan Trypanosoma cruzi. The available chemotherapy is restricted to two compounds: Nifurtimox and Benzonidazol. The T. cruzi life cycle occurs among invertebrate and vertebrate hosts and its survival strongly depends on its ability to catabolise both, carbohydrates and amino acids to obtain energy. The amino acids have an important role in several biological processes in this parasite. In this context, we studied the L-asparagine (Asn) relevance in the metabolism, differentiation and stress resistance of the T cruzi. Our results have shown that epimastigotes use Asn as carbon source, and contributes with the resistance to nutritional and oxidative stress. The Asn also showed a positive influence in metacyclogenesis and supported the ATP synthesis. Finally, the absence of Asn interfered with the proliferation of the replicative forms of T. cruzi. Taken together, our results suggest the involvement of the Asn metabolism in the protection of T. cruzi when submitted to different stress conditions.